Influence of the PMAQ program on the qualification of Primary Care: literature review (Research, Society and Development, 2022)
Objective: to understand about the influence of the PMAQ program on the qualification of Primary Care. Methodology: This study concerns a bibliographic review, of an integrative nature, with the data being summed up in a qualitative way. The sample was raised to support this review work, focusing on the specialized academic literature, based on data from the VHL, SCIELO and LILACS, which are the main research tools for articles of literary significance. Results: At first, in the general filter of the theme, 214 articles were found that addressed the topic of primary care based on the PMAQ-AB, after a systematic filter, 50 publications were found that addressed the proposed theme, and 07 articles were selected for discussion. After exploratory and critical reading, the articles were organized by title, journal, author, year and objective. Final considerations: The results of the PMAQ to improve access to health in most of the analyzed studies are evidenced in this study, demonstrating that this program is capable of provoking in professionals and managers more need to work with even more qualified actions and that make it possible for policies to public policies in health are fulfilled and expanded to meet the needs of the population, pointing out that this incentive influences the daily life of health.